Comparative study of the anti-inflammatory effect of plantago major "plantain" and diclofenac - Estacio, M. (2022)
We have determined the 50 Lethal dose of the Metanolic extract of Plantago major "Llanten" given by intraperitoneal route. We have found that 50LD was 4000 mg/Kg. Of animal weigtht, using 36 mice divided in six groups with 6 animal s each one. 40 rats divided in four groups of ten animals each one received on the back 2 mI of carragenin 1 % to the air pouch. After 30 minutes, the extract and diclofenac were administered. Six hours afterwards the animal s were killed. The exudate obtained was used to find the leucocyte count in the Coulter Counter. The rest of the material was centrifuged to determine the concentracion of proteins with de Gornall colorimetric method using the Biuret reactive and a model of protein lof 70 g/L. We found the anti-inflammatory properties of the methanolic extract, administered by the intraperitoneal route 400 mg/Kg. and 800mg/Kg and with diclofenac using the standardized technique of Edwards (CYTED) from the granuloma of .. Pouche